The impact of COVID-19 on the gender division of housework and childcare: Evidence from two waves of the pandemic in Italy - Daniela Del Boca; Noemi Oggero; Paola Profeta; Mariacristina Rossi (IZA Journal of Labor Economics, 2022)
The COVID-19 pandemic has had a dramatic impact on families' lives because of the increased demands of housework and childcare. Much of the additional burden has been shouldered by women. Yet, the rise in remote working also has the potential to increase paternal involvement in family life and thus to reduce gender role inequalities. This effect depends on the working arrangements of each partner, whether working remotely, at their usual workplace, or ceasing work altogether. Using two waves of an ad-hoc survey conducted in April and November 2020, we show that the time spent by women in domestic activities did not depend on their partners' working arrangements. Conversely, men spent fewer hours helping with housework and home schooling when their partners were at home. Although men who worked remotely or did not work at all devoted more time to household activities during the second wave of COVID-19, the increased time they spent at home did not seem to lead to a reallocation of couples' time.
Keywords: J13; J16; J21; 330; gender; housework; childcare; work arrangements; COVID-19